1988
DOI: 10.1016/0735-1097(88)90407-x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training after anterior Q wave myocardial infarction: Importance of regional left ventricular function and topography

Abstract: To determine whether the extent of left ventricular dysfunction and the degree of shape distortion can predict outcome in survivors of moderate-sized anterior Q wave myocardial infarction who are undergoing exercise training, these variables were measured by two-dimensional echocardiography before and after 12 weeks of a low level exercise training program starting 15 weeks after infarction in 13 patients (7 in group 1 and 6 in group 2) and 12 weeks apart in 24 matched control patients without training. By the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(81 citation statements)
references
References 33 publications
3
75
0
3
Order By: Relevance
“…In other words, endurance training following infarction, resulted in enhancement of cardiac hypertrophy. Previous studies have shown that endurance training after MI can have a beneficial effect (9,13,14), without affecting (6, 7, 10, 12) or adverse effects (11,15) on cardiac function and remodeling. The results of this study showed that endurance training running on a treadmill after MI increased the rate of necrosis damage and infarct size compared with the control group (no training).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, endurance training following infarction, resulted in enhancement of cardiac hypertrophy. Previous studies have shown that endurance training after MI can have a beneficial effect (9,13,14), without affecting (6, 7, 10, 12) or adverse effects (11,15) on cardiac function and remodeling. The results of this study showed that endurance training running on a treadmill after MI increased the rate of necrosis damage and infarct size compared with the control group (no training).…”
Section: Discussionmentioning
confidence: 99%
“…Serra et al (2010) suggested that 13-weeks of endurance training in rats, prevents adverse remodeling of LV that was caused by the injection of isoprenaline (14). Jugdutt et al (1988) claimed that 12-week low-intensity exercise after MI may trigger remodeling of LV, expansion of MI, further scar thinning and reduction of ejection fraction (15). In summary, many studies have been done with respect to the effects of endurance exercise training on cardiac remodeling after MI in animal and human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades several scientific works were published, which sought to assess the effects of the aerobic physical exercise on VR and the cardiac function of patients suffering from MI, who evolved with LV systolic dysfunction [7][8][9][10][13][14][15][16]. Many of these studies, considered classics and pioneers, continue to be cited in various scientific articles and are selected for composing meta-analyses, despite having been conducted at a time when blocking of neurohumoral activation after MI was not understood as the cornerstone of the treatment of ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Ornish et al found that patients in the exercise group demonstrated improved LVEF during peak exercise, 7 but Jugdutt et al reported that patients with lower LVEF developed further functional and topographic deterioration with exercise training. 6 Giannuzzi et al 5 reported that in the in EAMI trial post infarction patients without clinical complications, even those with a large infarction, had a possible benefit from long-term physical training without any additional negative effect on ventricular size or topography. Recently, Otsuka et al reported that patients with moderate to severe LV dysfunction benefited from exercise training started early after AMI without any deterioration in LV remodeling, with a similar magnitude of improvement in exercise capacity to that in patients with mild LV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…
everal studies have reported the influence of exercise training on left ventricular (LV) contractility in patients with myocardial infarction (MI), although consensus has not been obtained; no changes in resting contractility were observed, 1-4 improvement was achieved only in patients with cardiac dysfunction, 5 deterioration was observed only in patients with cardiac dysfunction, 6 LV ejection fraction (LVEF) during exercise improved. 7,8 The present study was conducted to investigate the influence of exercise training on LV function and exercise tolerance in patients with acute MI (AMI) using a new index of cardiac function, the Tei index.
…”
mentioning
confidence: 99%